1992
DOI: 10.3406/arsci.1992.895
|View full text |Cite
|
Sign up to set email alerts
|

De l'origine du cobalt dans les verres

Abstract: Le but de ce travail est l'étude de la provenance des colorants bleus au cobalt utilisés par les verriers, de l'Age du Bronze jusqu'au XVIIIe siècle. Les premiers résultats que nous présentons ici concernent essentiellement les verres médiévaux d'ateliers du sud et de l'est de la France. Ces résultats nous permettent à la fois de mettre en évidence l'existence de quatre principaux types de minerais de cobalt parmi les verres étudiés et de préciser les périodes d'utilisation et l'origine de certains d'entre eux. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 2 publications
6
81
0
Order By: Relevance
“…1560-1570), the presence of a considerable amount of arsenic was confirmed by previous PIXE analysis [6] and Raman signature was observed as such [9]. In fact, arsenic is a minor element commonly found in European cobalt ores: the Co/As ratio reaches 0.4 for the 16 th to 17 th century European glass and decreases to ~0.1 during the 18 th century [28,[51][52][53][54][55]. On the contrary, Asian cobalt ores are rich in manganese and iron [55][56][57][58] and require a firing under strong reducing atmosphere [59] to develop only the blue colour of Co 2+ ions [15].…”
Section: Pigmentssupporting
confidence: 50%
“…1560-1570), the presence of a considerable amount of arsenic was confirmed by previous PIXE analysis [6] and Raman signature was observed as such [9]. In fact, arsenic is a minor element commonly found in European cobalt ores: the Co/As ratio reaches 0.4 for the 16 th to 17 th century European glass and decreases to ~0.1 during the 18 th century [28,[51][52][53][54][55]. On the contrary, Asian cobalt ores are rich in manganese and iron [55][56][57][58] and require a firing under strong reducing atmosphere [59] to develop only the blue colour of Co 2+ ions [15].…”
Section: Pigmentssupporting
confidence: 50%
“…While Tel Anafa and Jebel Khalid reduced glass composition and decolourant technology are closely similar, at Tel Anafa strongly coloured vessels form the majority of the assemblage [65: pp. [19][20][21], whereas this is not the case for the Jebel Khalid assemblage. Jennings [31: p. 56] concluded from comparison of Beirut and Tel Anafa bowls that although they were made in the same regional tradition, there were stylistic differences that suggested different secondary workshops, which could have been supplied with glass by a single primary location.…”
Section: Inter-site Compositional Comparisonsmentioning
confidence: 99%
“…In both these regions the cobalt is associated with arsenic. 30,31 The cobalt ore in Germany is associated with Ag-bearing minerals and Ni, Bi, Zn or Mo are usually present. Recently, it has been shown that early primary glass production (high Al, high Ca glass) took place at Ile-Ife in southwestern Nigeria and utilized cobalt associated with high levels of manganese to manufacture dark blue beads.…”
Section: Pigmentsmentioning
confidence: 99%